Green credit policy, government behavior and green innovation quality of enterprises. (10th January 2022) - Wang, Hetong; Qi, Shaozhou; Zhou, Chaobo; Zhou, Jingjie; Huang, Xiaoyan
Abstract: This study takes Green Credit Guidelines in China as a quasi-natural experiment to examine its effect on the quality of green innovation in heavily polluting enterprises. Based on the data of Chinese listed companies from 2008 to 2019, DID model, and a series of robustness tests, findings show that Green Credit Guidelines significantly improve the quality of enterprises' green innovation. The positive effect is more significant in state-owned enterprises and those in the eastern region and less financially developed areas. The officials' promotion pressure and fiscal decentralization have negative and positive moderating effects, respectively. Additional analysis demonstrates that the quality improvement of enterprises' green innovation can further increase their economic returns. Specifically, the competitiveness and market value of enterprise products are enhanced. The results provide enterprises with theoretical guidance on how to deal with environmental regulation. The results also provide countries around the world, especially developing countries, with important reference to implement green credit policy to achieve sustainable development. Highlights: Green Credit Guidelines improve the quality of green innovation in enterprises. Promotion pressure has a negative moderating effect on the impact of Green Credit Guidelines, while fiscal decentralization has a positive one. Green Credit Guidelines can enhance the product competitiveness and market value of enterprises by improving the quality of green innovation.